Internationalization of MSMEs Based on Comparative Advantage (Case Study of Nipah Lidi and Palm Oil Exporters in East Kalimantan) - Dewi Wulan Sari; Imam Mukhlis (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Export activities carried out by small and medium-sized businesses have the potential to become a foreign exchange earner for the country as proclaimed. Often there are obstacles experienced by small and medium-sized businesses in carrying out these international trade activities. Extracted from several interviews with small and medium business owners, it was revealed that the obstacles faced were from the product itself, regarding quality and quantity. Both of these things often did not meet the mutually agreed standards. Another thing that becomes an obstacle is the difficulty of providing a container which is a vital aspect of the process of sending goods that are ready. Judging from the aspect of the theory of comparative advantage, the international trade activity should have a very bright potential to be developed so that it becomes a foreign exchange earner to be recommended with.